(untitled) (ELECTRICAL MACHINES, MATERIALS AND DRIVES — PRESENT AND TRENDS, 2025)
In this paper, some of the currently available software tools for simulating low-current electrical circuits are presented and analyzed. The purpose of using several types of software tools is to help future researchers in the field find the software tool that is best suited for the study and analysis of the operation of low-current electrical circuits. Simulations for a low-pass active filter in Butterworth topology are performed as an example. DOI: https://doi.org/10.36801/apme.2024.1.12